Frontpage of Freie Jugend (Berlin), 6, nr. 7. Dedication by E. Mühsam, dated June 30, 1920, on front
Frontpage of Freie Jugend (Berlin), 6, nr. 7. Dedication by E. Mühsam, dated June 30, 1920, on front.